PENERAPAN METODE ROUGH – ORDINAL LOGISTIC REGRESSION UNTUK PEMODELAN FAKTOR-FAKTOR YANG MEMENGARUHI TINGKAT STRES MAHASISWA DALAM PEMBELAJARAN JARAK JAUH [APPLICATION OF THE ROUGH – ORDINAL LOGISTIC REGRESSION METHOD FOR MODELING FACTORS AFFECTING STRESS LEVELS OF STUDENTS IN DISTANCE LEARNING] - Sari, Sulistya Umie Ruhmana; Sasongko, Dimas Femy (Universitas Pelita Harapan, 2022)
The COVID-19 pandemic has changed the whole way we live, especially in the field of education. Distance learning as a result of the COVID-19 pandemic has had a stressful effect on students. This study aims to model the factors that influence students' stress levels towards distance learning. A total of 256 students of the Faculty of Teacher Training at Maulana Malik Ibrahim Malang State Islamic University participated in answering a 4-scale Likert questionnaire that was analyzed using the ordinal logistic regression method. The results of the study prove that there are significant factors affecting student stress levels in distance learning during the pandemic. These factors are: (1) different environments between students and lecturers; (2) frequency of assignments; (3) difficulty in understanding the material; (4) strong internet connection; (5) difficulty in coordinating with groups; (6) non-fixed lecture schedules; (7) the number of activities at home; and, (8) internet quota needs. The power of association score R2 with the Nagelkerke method was obtained by 0.776 (77.6%) which means that 77.6% of the independent variables were able to explain the stress level of students.BAHASA INDONESIA ABSTRACT: Pandemi covid-19 telah mengubah keseluruhan cara hidup kita, khususnya bidang pendidikan. Pembelajaran jarak jauh sebagai dampak dari adanya pandemic covid-19 telah memberikan pengaruh stres pada mahasiswa. Penelitian ini bertujuan untuk melakukan pemodelan terhadap faktor-faktor yang mempengaruhi tingkat stres mahasiswa terhadap pembelajaran jarak jauh. Sebanyak 256 mahasiswa Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang berpartisipasi dalam menjawab angket Likert berskala 4 dan dianalisis dengan metode regresi logistik ordinal. Hasil penelitian membuktikan bahwa terdapat faktor signifikan mempengaruhi tingkat stres mahasiswa dalam pembelajaran jarak jauh di masa pandemi. Faktor-faktor tersebut adalah: (1) lingkungan yang berbeda antara mahasiswa dengan dosen; (2) intensitas pemberian tugas; (3) kesulitan memahami materi; (4) kelancaran akses internet; (5) kesulitan berkoordinasi dengan kelompok; (6) jadwal perkuliahan yang tidak tetap; (7) banyaknya kegiatan di rumah, dan (8) kebutuhan kuota internet. Nilai kekuatan asosiasi R2 dengan metode Nagelkerke diperoleh sebesar 0,776 (77,6%) yang menunjukkan bahwa 77,6 % variabel bebas mampu menjelaskan tingkat stres mahasiswa.